The Effects of Power Settings and Liquid Flavors on the Gravimetric Filter Correction Factors and Real-Time Measurements - Piner, Emma Grace; Perez, Gabriela (My University, 2024)
PM2.5 or fine particulate matter are particles that are 2.5 µm in size or smaller that are produced by electronic cigarettes (ECIGs). These particles can travel in deep parts of the lungs. The popularity has increased among young adults and teens making users and people around them more exposed to these particles. There is very limited research on looking at the second-hand exposure ECIGS produce. This study is being conducted to gain a better understanding of PM2.5 exposure effects by conducting measurements using real-time aerosol instruments that can quantify the exposure and capture the vaping behavior. The objective of this study is to determine the effects of three factors on these filter correction factors, including frequency of inhalation, flavorants, and ECIG device power. The ECIG device that will be used is the SMOK Novo X, which allows users to change the flavorant and power. Secondhand PM2.5 exposure will be generated inside a controlled laboratory chamber using a diaphragm pump and a timer to simulate user secondhand vaping. The variability in PM2.5 measurements and the filter correction values will be compared between these devices. Each experiment will be repeated three times for statistical significance, and a total of 60 experiments will be conducted to capture the inner variability between these factors. This study found within the real-time mass concentration that the mass concentration increased as the wattage went up and flavorant had no effect. The filter correction factors found that the pDR can perform better than the SMPS+APS due to these machines volatilizing the aerosol in the gas phase. The aerosol size distribution proved that the increase in wattages also led to a higher concentration of aerosol particles. This is a very big public health concern, and this study proves that ECIG aerosol particles increase in size as wattage increases which can cause harmful secondhand exposure effects.
Keywords: Particulate matter, PM2.5, ECIG, PG/VG ratios, Filter correction factors